Communication about Traditional Culture through Music Videos of Young Singers in Vietnam - Khang Tan Nguyen; Thach Hue Man (Ikatan Sarjana Komunikasi Indonesia, 2022)
The Vietnamese music market has recently welcomed the phenomenon of young artists using traditional Vietnamese cultural materials to create modern entertainment MV products. In this research, we use qualitative research to identify cultural factors appearing in MVs of two singers Bich Phuong and Hoang Thuy Linh. At the same time, the research team evaluates the effectiveness of integrating Vietnamese cultural elements in the music products of the two singers mentioned above by surveying students of University of Social Sciences and Humanities and Vietnam National University-HCM via a questionnaire. The survey results show that Vietnamese traditional culture is still a topic of interest to many young people. However, instead of learning through traditional channels such as schools and books, the public now has more choices and videos have become one of the most popular approaches thanks to the vivid combination of images and sound. Concurrently, the majority of students said that they regularly follow and watch newly released MVs from artists. The MVs carefully invested in terms of images and skillfully combined folk with modern materials will impress the public and inspire young people to get to know more about conventional values. Traditional culture is expressed through MV. Thereby, it can be seen that the integration of Vietnamese cultural elements into the MV is not only entertaining and educating, improving efficiency in preserving, preserving and spreading diverse and rich cultures, but also imbued with Vietnamese identity.